Оптимальне керування режимами розподільних електричних мереж з сонячними електростанціями при несиметричному навантаженні - Саченко, А. І.; Плєшков, С. П.; Плєшков, П. Г.; Зінзура, В. В.; Sachenko, A.; Plieshkov, S.; Plieshkov, P.; Zinzura, V. (ЦНТУ, 2022)
Робота присвячена удосконаленню системи автоматичного керування режимами роботи розподільних електричних мереж, що містять сонячні електростанції з метою досягнення одночасного зниження рівнів усталеного відхилення напруги, несиметрії напруг на затискачах електроспоживачів за умови максимізації рівня генерації електроенергії сонячною електростанцією. Показано, що таку задачу автоматичного керування найдоцільніше інтерпретувати як задачу багатокритеріальної оптимізації. Обґрунтовано метод вирішення цієї задачі багатокритеріальної оптимізації. Розв’язки зазначеної задачі багатокритеріальної оптимізації можуть бути покладені в основу роботи оптимальної системи автоматичного керування параметрами режиму розподільних електричних мереж, що містять сонячні електростанції. The article is devoted to improving the system of automatic control of modes of distribution electric networks containing solar power plants in order to achieve a simultaneous reduction of steady-state voltage deviations, voltage asymmetry at the terminals of consumers while maximizing the level of electricity generation by solar power plants. Ensuring normal permissible levels of electricity quality indicators in distribution networks is one of the most pressing issues that arise in the design and operation of modern distribution networks. Deterioration of the quality of electricity in electrical networks leads to the appearance of such negative phenomena, increase in additional losses in the elements of the electrical network, reduce the service life of electrical equipment, reduce the productivity of production equipment and others. The most significant negative impact on the functioning of the elements of electrical distribution networks, including electricity consumers, is observed with increasing levels of steady-state deviation and voltage asymmetry above the normative values. Modern solar inverters allow you to control the level of steady voltage deviation at the point of their connection to the mains. The design features of the construction of inverters of solar power plants allow them to change (within certain limits) not only the level of steady-state voltage deviation, but also to affect the level of voltage asymmetry and the parameters of the reactive power mode. In view of this, the task of improving automatic control systems for the distribution of electric networks with solar power plants, the implementation of which will take into account the multifunctional influence of solar inverters on the parameters of these networks is quite relevant. For the research, a fragment of a typical distribution electrical network with a nominal voltage of 10 kV was used, which contains a solar power plant that connects directly to the 10 kV busbars. The authors of the article set the problem of controlling the parameters of the mode of distribution electric network with solar power plants in the form of the problem of multicriteria optimization. An approach to solving this problem is also proposed, which is based on the method of solving problems of multicriteria optimization by approaching the utopian point in the space of criteria. Approximate calculations are carried out, which confirm the possibility of applying the proposed approach to the construction of systems for automatic control of the parameters of the mode of distribution electrical networks with solar power plants.
Optimal Control of the Modes of Distribution Electrical Networks With Solar Power Plants Under Unbalanced Load
Keywords: сонячні електростанції; багатокритеріальна оптимізація; показники якості електричної енергії; solar power plants; multi-criteria optimization; indicators of the quality of electrical energy